THEORETICAL BASES OF ANALYSIS OF RISKS OF TREE OF IDENTIFIERS STATE INFORMATIVE RESOURCES - Бучик, С. С. (Science-based technologies, 2016)
In the article the theoretical bases of analysis of risks of tree of identifiers of state informative resources are expounded. The authors show the absence of effective mechanism of realization of risk process of management in Ukraine on the state level. According to the previous researches a concept of the cube of Yudina-Buchyka is entered, on the basis of it the authors built the actually methodology of construction of classifier of threats to the state informative resources (the authors enter a concept «methodology of double three of security»). In continuation of subjects of security of state informative resources the authors certain the methodology of estimation of risks of safety of the information-telecommunications systems and networks in the context of international standards. Raising of task of determination of level of risk of state informative resources taking into account basic descriptions, that characterize him, is carried out: assets (state informative resources behave to that), threats, to vulnerability, counter-measures, from that a decision is determined in relation to security of certain state informative resource in case of possible realization on him of attack, list of attacks that can be realization on assets.